Kloridhalter i gran utmed en depositionsgradient för havssalter - Munter, Fredrik (2005)
The knowledge of the chloride content and its fluxes and patterns in trees is insufficient. Increased knowledge would be desirable, one of many reasons is to be able to more efficiently meet the problems that the substance causes in the pulp industry. The purpose of this study was to examine and describe the chloride concentration of Norwegian spruce (Picea abies L. Karst.) in the south of Sweden. Furthermore the aim was to be able to predict chloride concentration from readily measurable site factors. Samples were collected from 8 plots situated along a sea salt deposition gradient, from the Swedish west coast to the highlands of Småland. Influence by variables such as chloride deposition, amount of precipitation, site index, and age were examined. The results showed that the mean chloride concentration in Norwegian spruce within the study area was 28,6 mg Cl- /kg dry weight substance in the wood fraction and 10-40 times higher in the remaining fractions (bark, branches and needles). The chloride concentration showed no relation to the amount of deposited chloride. Instead there was a correlation between concentration and amount of precipitation, measured as throughfall. The trends and patterns between the different variables were not significant enough to be able to calculate the concentration of chloride on the basis of the site factors.